2007
DOI: 10.1093/ajcn/85.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nutritional and inflammatory markers in dialysis patients with reduced appetite

Abstract: Background: Anorexia is common in chronic kidney disease and worsens as the disease progresses. Sex hormones and inflammatory cytokines may be related to feeding behavior. Objective: We hypothesized that appetite would be related to inflammation and outcome in hemodialysis patients but that sex may account for differences in the symptoms associated with poor appetite. Design: A cross-sectional study was conducted in patients undergoing prevalent hemodialysis (n ҃ 223; 127 M; x Ȁ SD age: 66 Ȁ 14 y). Anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 48 publications
12
136
4
4
Order By: Relevance
“…Given the estimates of the regression coefficients in Table 2, it would appear that patients with increased IL-6 levels had a significantly lower daily energy intake over the duration of the study. KalantarZadeh et al (22) and Carrero et al (23) showed that the extent of anorexia is closely and directly related to the level of plasma proinflammatory cytokine concentrations, including IL-6. Similar associations between dietary intake and Numbers of surviving patients versus those who died during follow-up at each study visit are given in parentheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the estimates of the regression coefficients in Table 2, it would appear that patients with increased IL-6 levels had a significantly lower daily energy intake over the duration of the study. KalantarZadeh et al (22) and Carrero et al (23) showed that the extent of anorexia is closely and directly related to the level of plasma proinflammatory cytokine concentrations, including IL-6. Similar associations between dietary intake and Numbers of surviving patients versus those who died during follow-up at each study visit are given in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several investigators suggested that PEW is a consequence of chronic inflammatory processes in patients with renal insufficiency (14,15,17,18). The pathophysiological basis of inflammatory cytokines, and particularly of IL-6-induced PEW, may be increased protein catabolism (19,20) and/or resistance to the anabolic effect of growth hormone, which may contribute to the loss of strength and muscle mass (21); in addition, inflammation may affect appetite and eating behavior (22,23). It was recently suggested that interactions between inflammatory markers and sTWEAK (soluble TNF-like weak inducer of apoptosis) affect the nutritional status of prevalent HD patients; thus, significant reductions in markers of PEW (IGF-1 and handgrip strength) associated with high levels of both IL-6 and sTWEAK may provide an additional link between inflammation and PEW (24).…”
Section: Introductionmentioning
confidence: 99%
“…This is a post hoc analysis from a cohort of prevalent HD patients in the Stockholm region, described elsewhere in more detail (20,21). The inclusion period ranged from October 2003 until September 2004.…”
Section: Methodsmentioning
confidence: 99%
“…93 In addition, although obesity can be associated with muscle wasting and catabolism, 11 increased fat stores usually reflect well preserved energy stores and preserved appetite. 94 In this case, the overall protective nutritional effect presumably overrides the cumulative longterm metabolic adverse effects of obesity. Despite overwhelming epidemiologic data on this association, we believe that a generalization of this sort would actually be inappropriate, and additional consideration of certain phenotypic features is necessary for proper management of dialysis patients.…”
Section: Should Nephrologists Promote Weight Gain In Dialysis Patients?mentioning
confidence: 99%